Performance Evaluation of Public Services: A Development of Public Services Quality Measurement and Customer Satisfaction Model on Three Cities in Java - Gayatri, Gita; Astuti, Rifelly Dewi; Martdianty, Fanny; Daryanti, Sri (ASEAN Marketing Journal, 2021)
Decentralization in Indonesia was meant to aid in the shifting of power from the central government to local governments, with the main aim to increase public services towards a more expeditious, efficient, flexible, and high quality of services, changing the paradigm from a ‘served bureaucracy’ towards a ‘bureaucracy that serves’. This research will evaluate: first, the perception of public service consumers towards the quality of public/government services, second, the perceived value received from public services, as well as third, the measurement of their satisfaction level resulting from the quality of services delivered by local governments at city level in the three areas of the Java Island. The research will use triangulation methods: qualitative research will be conducted using focus group discussions whereas quantitative research will be conducted using surveys.The findings are: first, the ten dimensions of service quality for the public sector -i.e. tangibility, reliability, responsiveness, credibility, competence, understanding customers, access, security, communication, and courtesy- were all proven to form the service quality construct in the public service quality. Moreover the proposed model that depicts the relationship between public service quality, perceived value and satisfaction was also confirmed; hence provide an evaluation tool for public services in city level.